2018
DOI: 10.1083/jcb.201709007
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule imaging reveals dynamic biphasic partition of RNA-binding proteins in stress granules

Abstract: Niewidok et al. analyze the distribution and dynamics of RNA-binding proteins (RBPs) with single-molecule resolution in living neuronal cells, providing direct support for liquid droplet behavior of stress granules in living cells and revealing transient binding of RBPs in nanocores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 46 publications
19
94
0
Order By: Relevance
“…Fortunately, single-molecule tracking has recently emerged as a powerful tool for examining LLPS in vivo (51,111,112). Indeed, the strongest evidence for bacterial condensates to date comes from single-molecule tracking of proteins in polar microdomains in Caulobacter (113).…”
Section: Single-molecule Tracking As a Tool For Examining Llps In Vivomentioning
confidence: 99%
“…Fortunately, single-molecule tracking has recently emerged as a powerful tool for examining LLPS in vivo (51,111,112). Indeed, the strongest evidence for bacterial condensates to date comes from single-molecule tracking of proteins in polar microdomains in Caulobacter (113).…”
Section: Single-molecule Tracking As a Tool For Examining Llps In Vivomentioning
confidence: 99%
“…The observation that RNPs do not appear to fuse with other RNPs even when closely associated within the germ plasm aggregate underscores the potential for substructure in phase-separated organelles (Anderson and Kedersha, 2007;Jain et al, 2016;Mitrea and Kriwacki, 2016), possibly depending on differential affinities of aggregate components in relation to each other and the cytoplasm. Indeed, many known cases of homotypic interactions within RNPs involve protein-protein interactions involving low complexity domains or IDRs (Gilks et al, 2004;Kato et al, 2012;Toretsky and Wright, 2014;Lin et al, 2015;Niewidok et al, 2018), but RNA-RNA interactions may provide additional levels of complexity for the development of such substructure (Van Treeck et al, 2018).…”
Section: Germ Plasm Is Composed Of Homotypic Rnps That Aggregate Segmentioning
confidence: 99%
“…It has been reported that SGs are not homogenous and contain substructures. In particular, several studies support a model where SGs contain stable cores surrounded by a more dynamic shell (Cirillo et al, 2020;Jain et al, 2016;Niewidok et al, 2018). Previously, it was also shown in Drosophila embryos that gurken transcripts are translated on the outside edge of P-bodies, another type of membrane-less organelle, and not in their core (Davidson et al, 2016).…”
Section: Position Of Mrnas Within Sgs Is Similar For Translating and mentioning
confidence: 88%